Spectral CT in evaluating the therapeutic effect of transarterial chemoembolization for hepatocellular carcinoma: A retrospective study. Issue 52 (December 2017) - Wang, Jun; Shen, Jia lin
Abstract : Abstract: This study aimed to investigate the value of computed tomographic (CT) spectral imaging in evaluating the effect of transarterial chemoembolization (TACE). The records of 67 patients with hepatocellular carcinoma (HCC) who had undergone dynamic spectral CT before treatment were selected for the study. Iodine concentrations pretreatment in liver parenchyma, the HCC lesion(s), portal vein, and aorta were measured from the decomposition images. The normalized iodine concentrations (NIC) were calculated. All of them underwent plain scan or contrast-enhanced CT post-treatment (approximately 4–6 weeks after TACE). The values of arterial phase normalized iodine concentrations (AP NIC) before TACE correlated with the grades of lipiodol deposition in tumors ( r = 0.76, P < .001). However, there was no relationship between normalized iodine concentrations in the portal venous phase (PVP NIC) before TACE and the grade of lipiodol deposition ( r = 0.17, P = .17). Values of AP NIC in residual tumors pre-TACE were significantly lower than those in partial lesions with deposition of iodized oil. The threshold AP NIC of 0.18 yielded an AUC of 0.895, 83.33% sensitivity, 81.03% specificity, 83.33% positive predictive value (PPV), and 82.76% negative predictive value, respectively. The survival probability in patients with AP NIC values pre-TACE ≥ 0.18 was higher than those whose AP NIC values pre-TACE were < 0.18 ( P = .028). Spectral CT with quantitative analysis of AP NIC may help to evaluate the utility and predict the therapeutic effect of TACE. Values of AP NIC had high sensitivity and specificity for differentiating partial tumors with lipiodol deposition from those without lipiodol deposition.